Implementing an Investment Facilitation Framework for Development: Lessons from the Trade Facilitation Agreement - Mohammad Saeed (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
There are many commonalities between the Investment Facilitation Framework for Development (IFF4D) and the Trade Facilitation Agreement (TFA), including transparency, simplification, user-friendliness, and stakeholders' collaboration. The author shares key takeaways from the successful negotiations and implementation of the TFA that can guide the world community in the context of the IFF4D.
Keywords: 330